(untitled) (International Journal of Current Engineering and Technology, 2015)
5S is a systematic technique used by organizations comes from five Japanese words; Seiri (sort), Seiton (set in order), Seiso (shine), Seiketsu (standardize) and shitsuke (sustain). This system helps to organize a work place for efficiency and decrease wasting and optimize quality and productivity via monitoring an organized environment. 5S is the pre-step of Total Productive Maintenance (TPM), is a systematic approach providing the contribution of all personnel in the cleaning regime of the company. 5S execution is an essential prerequisite of implementation of Total Productive Maintenance (TPM). In this paper relations between 5S and pillars of TPM are explicated. The objective of this study is to identify the effectiveness of 5S practices on the TPM implemented organization performance. The result of this study confirms that all 5S principles affect TPM directly or indirectly. Consequently, 5S is an effective tool which strongly supports the objectives of TPM implemented organization to achieve continuous improvement and higher performance.